2013
DOI: 10.1016/j.susc.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Valence band electronic structure characterization of the rutile TiO2 (110)-(1×2) reconstructed surface

Abstract: The electronic structure of the TiO 2 (110)-(1x2) surface has been studied by means of angular resolved ultraviolet photoemission spectroscopy (ARUPS). The valence band dispersion along the high symmetry surface directions, [001] and [1-10], has been recorded. The experimental data show no dispersion of the band-gap Ti 3d states. However, the existence of dispersive bands along the [001] direction located at about 7eV below the Fermi Level is reported. The existence of two different contributions in the emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
7
22
0
Order By: Relevance
“…These results are in good agreement with a UPS study by Sánchez-Sánchez et al [16], which found that the Ti 3+ 3d derived gap state located at 1.2 eV BE is only present on the (1×2) reconstructed TiO 2 (110) surface.…”
Section: Cits On the Cross-linked (1×2) Reconstruction Of Rutile Tio supporting
confidence: 92%
See 2 more Smart Citations
“…These results are in good agreement with a UPS study by Sánchez-Sánchez et al [16], which found that the Ti 3+ 3d derived gap state located at 1.2 eV BE is only present on the (1×2) reconstructed TiO 2 (110) surface.…”
Section: Cits On the Cross-linked (1×2) Reconstruction Of Rutile Tio supporting
confidence: 92%
“…The peak at -1.6 V was assigned to the (1×2) row and that at -1 V was assigned to defects in the band gap with the same origin as the peak found in UPS for lightly reduced TiO 2 (110). These two peaks presumably correspond to the minor and major peaks in the work of Sánchez-Sánchez et al [16].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Transition metal oxides have tremendous importance in a wide variety of technological applications such as heterogeneous catalysts, (photo-)electrodes, and gas sensors [1][2][3][4] . Among them, titanium dioxide (TiO 2 ) has also become the prototype material for surface science studies largely due to its ordered structure and capability of conduction upon reduction 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations for the different binding energies are that the oxygen vacancies are located at different lattice sites and/or forming clusters [33], or the existence of different types of defects [35,36].…”
mentioning
confidence: 99%